The role of the neural NO synthase adapter protein in the pathogenesis of metabolic syndrome and type 2 diabetes mellitus - L. A. Kuznetsova; N. E. Basova (Сибирский научный медицинский журнал, 2023)
The pathogenesis of metabolic syndrome (MS) is characterized by obesity, hypertension, dyslipidemia and insulin resistance. MS increases the risk of developing type 2 diabetes mellitus (DM2). The neuronal isoform of nitric oxide synthase (nNOS) is defined by complex protein-protein interactions, since nNOS, unlike other isoforms of NOS,contains a C-terminal PDZ domain, which allows it to conjugate with other proteins and, first of all, to interact with an adapter of neuronal, or type 1, nitric oxide synthase (NOS1AP), also denoted CAPON in our work. Changes in the interaction between nNOS and NOS1AP lead to metabolic disorders in brain, heart, liver and skeletal muscles, which plays a key role in the development of MS and T2DM. NOS1AP, interacting with the PDZ domain of nNOS, competes with the postsynaptic density protein (PSD95) and regulates the stability of subcellular localization of nNOS and enzyme expression during synapse formation. NOS1AP promotes nNOS binding to targets such as small GTPase (Dexras1), synapsines, regulating the formation of dendritic roots, mediates activation of the nNOS-p38MAP kinase pathway during excitotoxicity. It has been shown that single-nucleotide polymorphism of the NOS1AP gene and its overexpression in the myocardium leads to the manifestation of long QT syndrome, which is most clearly manifested in elderly patients with DM2. It was found that the genetic polymorphism of NOS1AP affects insulin secretion when using calcium blockers, and can promote the development of DM2. The functional role of NOS1AP in stabilizing the functions of skeletal muscle nNOS in the cytoskeletal complex associated with dystrophin/utrophin was discovered. The purpose of the review is to provide updated information on the role of NOS1AP and the nNOS/NOS1AP complex in the pathogenesis of MS and DM2. The potential molecular mechanisms of the interaction of NOS1AP with nNOS and with other proteins, which leads to change in nNOS activity, localization and content, are discussed.